2017
DOI: 10.1016/j.jstrokecerebrovasdis.2016.08.033
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Rates and Determinants of Poststroke Systolic Blood Pressure Control among Ghanaians

Abstract: A third of stroke survivors had SBP not on target during follow-up possibly due to a combination of therapeutic inertia, apparent treatment resistance, and poor adherence to therapy. Longer-term prospective interventional studies on hypertension control among stroke survivors are warranted in sub-Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…A recent study among Ghanaian stroke survivors identified up to 35% with less than optimal blood pressure control within the first year of stroke. (50) However, none of the traditional vascular risk factors were independently associated with VCI in this Ghanaian population, although regular physical activity seemed to confer some protection against VCI in unadjusted analysis. Interestingly regular physical activity which protects against stroke occurrence (44) has also been shown to be protective against VCI (51) potentially via enhanced cerebral perfusion and the elaboration of growth factors (51).…”
Section: Discussionmentioning
confidence: 72%
“…A recent study among Ghanaian stroke survivors identified up to 35% with less than optimal blood pressure control within the first year of stroke. (50) However, none of the traditional vascular risk factors were independently associated with VCI in this Ghanaian population, although regular physical activity seemed to confer some protection against VCI in unadjusted analysis. Interestingly regular physical activity which protects against stroke occurrence (44) has also been shown to be protective against VCI (51) potentially via enhanced cerebral perfusion and the elaboration of growth factors (51).…”
Section: Discussionmentioning
confidence: 72%
“…Among hypertensive patients on treatment in the present cohort, we have identified poor adherence to antihypertensive therapy, difficulties obtaining antihypertensive medications, longer duration of hypertension diagnosis, receiving healthcare at tertiary centers and number of antihypertensive medications to be independently associated with poor BP control [ 36 ]. Among Ghanaian stroke survivors with hypertension attending a neurology clinic, approximately 70% were found to have controlled BP during the first year after stroke [ 37 ]. Designing interventions aimed at improving medication adherence such as using mobile health technology [ 38 , 39 ] and cardiovascular polypill with generic antihypertensive medications [ 40 , 41 ] in resource-limited settings could lead to improvements in BP control.…”
Section: Discussionmentioning
confidence: 99%
“…The average duration from stroke onset to enrollment into our clinic was approximately 1 month and most patients were on secondary preventive interventions at presentation and we were either optimized or maintained existing therapies (16). Indeed among this cohort, we have previously reported systolic blood pressure control rates of up to 70% within the first year after stroke (21) with high rates of compliance with evidence-based secondary prevention cardiovascular medication utilization (22). In the Community based study in Tanzania, crude case fatality rate at 3 years was 60% (9).…”
Section: Discussionmentioning
confidence: 89%